2022
DOI: 10.3390/w14152342
|View full text |Cite
|
Sign up to set email alerts
|

Visualization Assisted Approach to Anomaly and Attack Detection in Water Treatment Systems

Abstract: The specificity of the water treatment field, associated with water transmission, distribution and accounting, as well as the need to use automation and intelligent tools for various information solutions and security tools, have resulted in the development of integrated approaches and practical solutions regarding various aspects of the functioning of such systems. The research problem lies in the insecurity of water treatment systems and their susceptibility to malicious influences from the side of potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the article, we considered visualization models as an alternative to graphs as a component of human–machine interaction, inspired by the visualization approaches used in bioinformatics. Despite their low prevalence, it has been shown that they can be an alternative to the established methods of presenting data in various application areas, such as transport systems [ 34 , 98 ], water supply management systems [ 99 ], critical infrastructures [ 100 ], mobile payment systems [ 101 ], social networks [ 102 ], and digital forensics [ 103 ]. The specificity of each model was shown, and the models leveled out the shortcomings in each other.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, we considered visualization models as an alternative to graphs as a component of human–machine interaction, inspired by the visualization approaches used in bioinformatics. Despite their low prevalence, it has been shown that they can be an alternative to the established methods of presenting data in various application areas, such as transport systems [ 34 , 98 ], water supply management systems [ 99 ], critical infrastructures [ 100 ], mobile payment systems [ 101 ], social networks [ 102 ], and digital forensics [ 103 ]. The specificity of each model was shown, and the models leveled out the shortcomings in each other.…”
Section: Discussionmentioning
confidence: 99%